2016
DOI: 10.18632/oncotarget.9047
|View full text |Cite
|
Sign up to set email alerts
|

COMMD7 is correlated with a novel NF-κB positive feedback loop in hepatocellular carcinoma

Abstract: The correlation between nuclear factor-kappa B (NF-κB) and COMMD7 in hepatocellular carcinoma (HCC) development remained unclear. Here, our clinicopathological data showed that COMMD7 is overexpressed in HCC with a correlation to NF-κB. Using HepG2 and SMMC-7721 cells that aberrantly overexpressed COMMD7, we found that NF-κB directly binds with COMMD7 promoter and serves as an activator for COMMD7 transcription by luciferase reporter assay, chromatin immunoprecipitation (ChIP), and electrophoretic mobility shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Our previous research has shown that COMMD7 is correlated with a novel NF-κB-positive feedback loop in HCC cells. Moreover, NF-κB directly binds to the COMMD7 promoter and serves as an activator for COMMD7 transcription 25 . Inconsistent with our previous findings, reports indicated that COMMD7 binds to the IκB kinase alpha (IKK) complex through NEMO and induces degradation of p65 leading to the termination of NF-κB signaling 19, 26.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our previous research has shown that COMMD7 is correlated with a novel NF-κB-positive feedback loop in HCC cells. Moreover, NF-κB directly binds to the COMMD7 promoter and serves as an activator for COMMD7 transcription 25 . Inconsistent with our previous findings, reports indicated that COMMD7 binds to the IκB kinase alpha (IKK) complex through NEMO and induces degradation of p65 leading to the termination of NF-κB signaling 19, 26.…”
Section: Discussionsupporting
confidence: 49%
“…Among the members of the COMMD family, COMMD1 has been the most extensively characterized and operates as a terminator of NF-κB signaling; 20 COMMD1 reduction is associated with cancer progression caused by constitutive NF-κB activation 21, 22. Another member of the COMMD family, COMMD7 has been identified as a novel NF-κB essential modulator (NEMO)-interacting protein and was reported to function as molecular target in several types of cancers including pancreatic ductal adenocarcinoma 23 and HCC24, 25 in our previous studies. Moreover, we previously found that COMMD7 positively correlated with the expression of NF-κB, and that the NF-κB signaling pathway could mediate the proliferative and anti-apoptotic effects of COMMD7 in HCC cells.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, COMMD7 was identified as a novel NEMO interacting protein involved in NF-κB signaling termination [ 7 ], the incorrect regulation of which is known to be associated with a variety of tumors [ 5 , 8 ]. One study demonstrated that COMMD7 played a dual regulatory role in the NF-κB signaling pathway in HCC [ 9 ]. However, to date, the expression of COMMD7 in AML and its prognostic value remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The human hepatocellular carcinoma cell lines Hepg2, MHCC97H, HuH7, and Bel-7402, and the live cell line L-02, and human embryonic kidney 293 (HEK-293) cells were purchased from Cell Bank of Shanghai Institute of Biochemistry and Cell Biology, Chinese Academy of Sciences. As previous described (22), cells were cultured in RPMI-1640 medium (Hyclone, Logan, uT, uSA) and supplemented with 10% fetal bovine serum (gibco, Carlsbad, CA, uSA), 1% penicillin/streptomycin at 37˚C in 5% Co 2 .…”
Section: Methodsmentioning
confidence: 99%